2015
DOI: 10.3390/ijms16024136
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of 1-Aminocyclopropane-1-carboxylic Acid Synthase Genes in Hevea brasiliensis

Abstract: Ethylene is an important factor that stimulates Hevea brasiliensis to produce natural rubber. 1-Aminocyclopropane-1-carboxylic acid synthase (ACS) is a rate-limiting enzyme in ethylene biosynthesis. However, knowledge of the ACS gene family of H. brasiliensis is limited. In this study, nine ACS-like genes were identified in H. brasiliensis. Sequence and phylogenetic analysis results confirmed that seven isozymes (HbACS1–7) of these nine ACS-like genes were similar to ACS isozymes with ACS activity in other pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…However, the expression of these gene families, especially that of SAMS (>fivefold) and ACO (>10-fold) is much lower in latex than other tissues. Such low expression or a lack of expression has been noticed recently for nine ACO genes in Hevea latex 35 . These results, together with the low oxygen condition in latex 36 and the requirement of oxygen by ACO to produce ethylene 34 , point out a weak ethylene-synthesizing ability in laticifers.…”
Section: Resultsmentioning
confidence: 99%
“…However, the expression of these gene families, especially that of SAMS (>fivefold) and ACO (>10-fold) is much lower in latex than other tissues. Such low expression or a lack of expression has been noticed recently for nine ACO genes in Hevea latex 35 . These results, together with the low oxygen condition in latex 36 and the requirement of oxygen by ACO to produce ethylene 34 , point out a weak ethylene-synthesizing ability in laticifers.…”
Section: Resultsmentioning
confidence: 99%
“…Ethylene biosynthesis and signalling pathways are particularly affected by ethephon stimulation. Following the first isolation of ethylene biosynthesis genes 33 , 34 , a genome-wide analysis showed that the Hevea genome activated 8 genes encoding S-adenosyl-L-methionine synthase (SAMS), 14 genes encoding 1-aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS) and 16 genes encoding ACC oxidase (ACO) 23 . Although 7 ACS and 8 ACO contigs were identified in the present RNA sequencing analysis, a small number of counts confirmed previous assumptions of low ethylene production in latex 23 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the patterns of cis -elements present among the promoter and intronic regions decide the levels of gene expression (Rombauts et al, 2003; Brown et al, 2007; Zou et al, 2011; Hernandez-Garcia and Finer, 2014), and any mutation(s) occurring in this region can greatly influence the stress-responsiveness of the coded genes (Wittkopp and Kalay, 2012). Most notably, diverse forms of stress may activate similar cis -element TF regulatory networks (Faktor et al, 1996; Kim et al, 2006; Soltani et al, 2006; Mellway et al, 2009; Cao et al, 2012; Payyavula et al, 2013; Ahn et al, 2014; Chen et al, 2015; Zhu et al, 2015). Despite having a great depth of understanding on plant stress and its significance in connecting diverse pathways, not many reports are available that connect the primary and specialized metabolism at the transcriptional level.…”
Section: Stress Conditions Regulating Primary and Specialized Metabolmentioning
confidence: 99%
“…This subfamily of MYB proteins is known to bind to the MYB-recognizing elements ( MREs having the consensus sequence ANCNNCC, as demonstrated in MBSI, MBSII and MBSIIG; Franco-Zorrilla et al, 2014; Zhu et al, 2015), regulate Phenylpropanoid metabolism in plants (Liu et al, 2015). Additionally, R2R3-MYBs have been associated with several pleiotropic roles, like cell wall synthesis, regulation of pollen wall composition, glucosinolate biosynthesis, developmental processes, responses to physiological stress and determination of cell fate and identity (Lu et al, 2002; Du et al, 2012; Cao et al, 2013; Höll et al, 2013; He et al, 2016; Gates et al, 2016).…”
Section: Stress Conditions Regulating Primary and Specialized Metabolmentioning
confidence: 99%